349 Locally Recurrent GBM Treated with Resection and Immediate Initiation of Radiation Therapy: Results from a Prospective Trial. (1st April 2022) - Smith, Kris; Nakaji, Peter; Thomas, Theresa; Pinnaduwage, Dilini; Wallstrom, Garrick; Brachman, David
Abstract : INTRODUCTION: Treatment for recurrent GBM remains problematic. Resection (R) alone is insufficient, and survivals achieved with systemic therapy with or without radiation therapy (RT) are typically <1 year. METHODS: From 2/2013-2/2018, locally recurrent GBM were treated in a single arm trial (ClinicalTrials.gov, NCT#03088579) of R plus implantation of a surgically targeted radiation therapy (STaRT) device utilizing Cs-131 in bioresorbable collagen tiles (GammaTile, GT Medical Technologies, Tempe AZ USA). RESULTS: 28 patients (pts) were treated, 20 at first recurrence (range 1-3). Median age 58 (range 21-80), KPS 80 (60-100), female:male ratio 10:18. Median OS 10.7 mo., radiographic LC 8.8 mo., and no first failure was local. MGMT, KPS, and sex were non-predictive. Post hoc analysis disclosed after R+STaRT, 17 pts (54%) received >1 cycle of systemic (Sys) treatment ("Sys+") and 13 pts (46%) did not ("Sys- "). Sys was given as adjuvant, salvage, or both, either alone or in combination. 15 pts received bevacizumab (BEV), 12 temozolomide (TMZ) and 8 lomustine (CCNU). Median OS (mo.) for Sys+ vs. Sys- was 15.1/6.5 (hazard ratio (HR) .38, p = .017); OS for BEV+ vs. BEV- was 16.7/4.5 (HR .38, p = .017), TMZ+ vs. TMZ- 17.5/6.7 (HR .40, p = .025) and for CCNU+ vs. CCNU- 17.5/7.9 (HR .61, p = .25), respectively. LC was 11.4 mo. for Sys+ vs. 2.1 mo. for Sys- (HR .44; p = .16). Three attributed serious AE occurred, 1 wound infection requiring surgery and 2 radiation brain effects, managed medically. CONCLUSION: Post hoc analysis suggests R+STaRT+Sys may have the potential to impact OS in locally recurrent GBM, possibly by allowing sufficient time for biologically slower but effective treatments to have an impact.